2004
DOI: 10.1598/rt.58.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Student Interest With the Imagine, Elaborate, Predict, and Confirm (IEPC) Strategy

Abstract: In order to make predictions about a text, students must have prior knowledge or experiences about the topic and a means or a reason to retrieve this latent information and knowledge. The Imagine, Elaborate, Predict, and Confirm (IEPC) strategy takes the predictive process back to its origins in the imagination and extends it throughout the prereading, reading, and postreading stages of a lesson. The strength of IEPC appears to be in the whole‐class participation aspect, which enables the teacher to guide, foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The use of appropriate visual materials (i.e., realistic pictures depicting the contents of a text) can also be beneficial to educators for identification of teaching tasks, such as line drawings for teaching activities (Kleinman & Dwyer, 1999), and to those students who have basic knowledge for the tasks (Lowe, 1996;Wood & Endres, 2004).…”
Section: The Role Of Unconscious Mental Imagery In the Educational Immentioning
confidence: 99%
See 2 more Smart Citations
“…The use of appropriate visual materials (i.e., realistic pictures depicting the contents of a text) can also be beneficial to educators for identification of teaching tasks, such as line drawings for teaching activities (Kleinman & Dwyer, 1999), and to those students who have basic knowledge for the tasks (Lowe, 1996;Wood & Endres, 2004).…”
Section: The Role Of Unconscious Mental Imagery In the Educational Immentioning
confidence: 99%
“…The visual system thus enhances memory processes, visual abilities, and thinking skills, thereby increasing the effectiveness of teaching and learning performance (Hegarty & Just, 1993;Levie & Lentz, 1982). Wood and Endres (2004) suggested that as students develop their visual ability to imagine, elaborate, predict, and confirm, they grasp the meaning of information more comprehensively. This is because the system allows students to acquire and make sense of information unconsciously, providing an alternative to conscious information acquisition (Winn, 1987).…”
Section: The Role Of Unconscious Mental Imagery In the Educational Immentioning
confidence: 99%
See 1 more Smart Citation
“…While some researchers' definitions or references suggest visual images lead to imagination (Maine, 2013;McTigue, 2010;Serafini & Moses, 2014), other researchers suggest multi-sensory input affects imagination (Douville & Algozzine, 2004;Hannaford, 2012;Roser et al, 2004;Wood & Endres, 2004). Hannaford suggests imagination forms a bridge between the reader's senses and thoughts (Hannford, 2012).…”
Section: Significancementioning
confidence: 99%
“…The 'RIDER' procedure (Clark, Deshler, Schumaker, Alley, & Warner, 1984) teaches students to read the first sentence or section of the text, make an image of it, describe the image, evaluate it for its completeness and repeat the steps for the following sentences. The IEPC strategy (Wood & Endres, 2005) teaches a four-step procedure as one reads: to imagine, elaborate, predict and confirm.…”
Section: Teaching the Comprehending Strategiesmentioning
confidence: 99%